Are cervical curvature and axioscapular muscle activity associated with disability in patients with chronic nonspecific neck pain? – a cross sectional exploratory study - Huang, Yanfeng; Elabd, Aliaa M.; Adams, Roger; Elabd, Omar M.; Torad, Ahmed A.; Han, Jia (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose To ascertain the relationship between cervical curvature, neck muscle activity and neck disability in patients with chronic nonspecific neck pain (CNNP). Methods Ninety participants (mean age = 27.2, female/male ratio = 7/2) with CNNP volunteered. The Neck Disability Index was used to assess neck disability. To indicate the electromyographic characteristics of the axioscapular muscles, the root mean squares and median frequencies of upper trapezius and levator scapula were used. Cervical curvature was measured with a flexible ruler. Results Disability of the neck was significantly correlated with curvature (r = −0.599, p < 0.001), upper trapezius root mean square (RMS) (r = 0.694, p < 0.001) and levator RMS (r = 0.429, p < 0.05). Multiple regression analysis produced a significant predictive equation that could predict disability: 33.224− 0.515 × Curvature + 0.156 × Levator RMS − 0.059 × Upper trapezius median frequency + 0.636 × upper trapezius RMS + 0.020 × levator median frequency, with R2 = 0.622. Conclusion Cervical curvature as well as different axioscapular muscle activity were found to be related to level of disability. These findings have implications for clinical management of CNNP.